Association of clinical features of acute viral encephalitis with mortality and neurodevelopmental outcomes (Northern International Medical College Journal, 2015)
Background : Acute viral encephalitis is a world-wide health problem with severe morbidity, significant mortality and a high incidence of residual sequelae in survivors.Objective : To identify the association of clinical features of acute viral encephalitis with mortality and neurodevelopment outcomes.Methodology : It is a hospital based comparative observational prospective study done in Dhaka Shishu Hospital during the period of October 2005 to March 2006. Children with 1 month to 12 years of both sex presenting with specific clinical features and laboratory evidences suggestive of acute viral encephalitis (seizures, altered consciousness, features of raised intracranial pressure, cerebrospinal fluid evidences of viral encephalitis) were included. 44 children were enrolled according to inclusion criteria. Data were collected on clinical and socio demographic status. SPSS 16 version program was used for data analysis.Result : Among the 44 cases, the mean age bellow 2 years was 14 months and above 2 years was 66 months. The incidence of acute viral encephalitis was highest within first 3 years of age. Most of the mortality 8(72.73%) occurred in low income group (P=0.003). 29(66 %) patients had Glasgow Coma Score